Validation of a multidisciplinary care protocol for critically ill patients with delirium - Thieli Lemos de Souza; Karina de Oliveira Azzolin; Emiliane Nogueira de Souza
ABSTRACT Objective: To validate a multiprofessional protocol for the care of patients with delirium admitted to an intensive care unit. Method: Methodological study with the purpose of confirming with experts the care recommendations proposed in the protocol. For the content validation process, the content validity index of ≥ 0.90 was considered. Results: Of the 48 recommendations submitted to content validation, only four did not reach consensus through the content validity index. The multiprofessional protocol for patients with delirium in the intensive care unit included care related to the diagnosis of delirium, pause in sedation, early mobilization, pain management, agitation and delirium, cognitive guidance, sleep promotion, environmental interventions, and family participation. Conclusion: The multiprofessional protocol qualifies the care provided to critically ill patients with delirium, improving clinical outcomes.